Investigação sobre fatores preditores do desempenho em decisão lexical em segunda língua - Vieira, Paula Ribeiro (2015)
Word recognition is an important skill for reading. Development of vocabulary enables more fluent and accurate reading. The aim of this study was to investigate individual differences in working memory capacity and vocabulary size in a second language and their association with the lexical access. The participants were Brazilian late learners of English as a second language. The lexical decision task involved recognition and judgment of words; the task was to decide whether the word existed or not. The task consisted of 120 items, of which there were 60 words, 30 pseudowords and 30 non-words. The study included 28 subjects, all adults; 14 were begginer-level in English, and 14, advanced level. The main goals were to investigate: (1) if individual differences in working memory capacity are associated with the lexical decision; (2) whether vocabulary size predicts participants’ performance in the lexical decision task. The results showed that vocabulary size was associated with the accuracy in identifying pseudowords. Working memory capacity was not significantly associated with the performance on the lexical decision task. For lexical decision by late learners of L2, thus, the study identified a role of vocabulary size, as expected. Individual differences in working memory capacity were not associated with the performance on the lexical decision task.